1992
DOI: 10.1177/026988119200600306
|View full text |Cite
|
Sign up to set email alerts
|

The effects and after effects of the α2-adrenoceptor antagonist idazoxan on mood, memory and attention in normal volunteers

Abstract: Idazoxan, an α( 2)-adrenoceptor antagonist, is an effective antidepressant with a mode of action different from that of conventional antidepressants. As it is used as an antidepressant it is important to know whether there are any unwanted CNS side effects. Study of its effects will also provide information on the relationship between noradrenergic function and mood and performance. Twelve normal male volunteers who were given the drug (40 mg orally three times daily for 21 days) were compared with 12 matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…3,4,5), an observation consistent with their recognized stimulant properties (Aghajanian et al 1977;Sara and Devauges 1989;Levin 1992;Smith et al 1992). In addition, changes in cognitive function induced by both nicotine (Levin 1992) and α 2 -adrenergic drugs (Arnsten and Goldman-Rakic 1985;Arnsten et al 1988) appear to involve inverted-U dose-effect relationships, a pattern consistent with the facilitation observed after 0.083 mg / kg and the disruption after 0.75 mg / kg of nicotine (Fig.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…3,4,5), an observation consistent with their recognized stimulant properties (Aghajanian et al 1977;Sara and Devauges 1989;Levin 1992;Smith et al 1992). In addition, changes in cognitive function induced by both nicotine (Levin 1992) and α 2 -adrenergic drugs (Arnsten and Goldman-Rakic 1985;Arnsten et al 1988) appear to involve inverted-U dose-effect relationships, a pattern consistent with the facilitation observed after 0.083 mg / kg and the disruption after 0.75 mg / kg of nicotine (Fig.…”
Section: Discussionsupporting
confidence: 73%
“…Thus treatment with the 2 -adrenergic agonist clonidine reduces noradrenergic activity (Starke et al 1974) and yields behavior consistent with reduced arousal (e.g., sedation and analgesia: Meyer et al 1977;Tilson et al 1977). Conversely, treatment with the 2 -adrenergic antagonist idazoxan tends to increase noradrenergic activity (Aghajanian et al 1977) and has been associated recently with improvements in memory (Sara and Devauges 1989) and attention (Devauges and Sara 1990;Smith et al 1992;Bunsey and Strupp 1995). These findings, as well as increased distractibility in the 5-CSRT task produced by lesions of the dorsal noradrenergic bundle (Carli et al 1983;Cole and Robbins 1992), led to the prediction that idazoxan will enhance, and clonidine impair, signal detection.…”
Section: Introductionmentioning
confidence: 99%
“…At higher doses in man, Coull et al (1995a) found some signiÞcant improvements in performance of CANTAB tests sensitive to frontal lobe dysfunction. Improvements in aspects of executive performance have also been found following administration of the a 2 -antagonist, idazoxan, which elevates functional noradrenaline levels (Smith et al 1992). Thus, there is evidence to suggest that noradrenaline also plays a role in frontal lobe function.…”
Section: Discussionmentioning
confidence: 98%
“…Low, presynaptically active doses of clonidine may interfere with learning by reducing adrenergic activity (Arnsten and Goldman-Rakic 1985). Conversely, low but not high doses of ez-adrenoceptor antagonists such as yohimbine and idazoxan also appear to enhance memory retention and recall (Smith et al 1992). Sara and her co-workers showed improved recall of old memories of a linear maze task by rats tested immediately after administration of amphetamine and idazoxan (Sara and Devauges 1989;Devauges and Sara 1990).…”
Section: Adrenergic Enhancementmentioning
confidence: 99%